Conversations in human evolution. - Timbrell, Lucy, (Access archaeology., 2021)
This second volume reports another twenty interviews with scholars at the forefront of human evolution research, covering the broad scientific themes of Palaeolithic archaeology, palaeoanthropology and biological anthropology, earth science and palaeoclimatic change, evolutionary anthropology and primatology, and human disease co-evolution.